Profil Kemampuan Berpikir Kreatif Mahasiswa dalam Mengajukan Masalah Persamaan Diferensial - Wasilatul Murtafiah (Universitas PGRI Madiun, 2017)
Problem Posing approach is necessary for teacher training students. Problem Posing can train students to create questions/problems and their solutions. Make problem then solve it is part of student’s creative thinking ability. Differential equations problem is one of the materials that learned in mathematics education courses. Every teacher training student of mathematics has diverse skills. This diversity certainly brings various creative thinking skills as well. The purpose of this study is to determine the ability of student’s creative thinking in mathematical education courses, differential equation problem posing. This study uses a qualitative approach with descriptive methods. Sources of data in this study are the students of mathematics education consist of one student of each with high, medium, and low begining math ability. The data collection was conducted by using observation, testing, and interviews. Technique authenticity of data using a triangulation method. Data analysis technique done in stages, data reduction, data presentation, drawing conclusions, and verification. The result of this study were (1) Students with high initial capability not have fluency and flexibility of thought, but it shows the novelty think that qualifies as a Creative Thinking Ability Level (CTAL) 2 is creative enough, (2) Students with prior knowledge currently have the fluency of thought, but do not have the flexibility and novelty think that qualifies as a Level capabilities creative thinking (CTAL) 1 is less creative, (3) Students with prior knowledge low yet has grace, eloquence, and the novelty of thought that goes into the criteria of creative thinking ability Level (CTAL) 0 is not creative.